2020
DOI: 10.1097/pec.0000000000001379
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Rates in Pediatric Emergency Medicine Physicians

Abstract: Objective Burnout is a syndrome in which a reduced sense of personal accomplishment, depersonalization, and emotional exhaustion develop in response to prolonged stress. It is well known that physicians suffer high rates of burnout; emergency medicine physicians experience significantly increased rates of burnout, whereas physicians in other specialties, like pediatrics, may be spared. Pediatric emergency medicine physicians are on the frontline of care for the critically ill child, which could put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…The prevalence of BO in PEM physicians has been previously reported at 25% to 88.5% . The prevalence of BO in our study population falls just below the lower end of this range.…”
Section: Bomentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of BO in PEM physicians has been previously reported at 25% to 88.5% . The prevalence of BO in our study population falls just below the lower end of this range.…”
Section: Bomentioning
confidence: 99%
“…The prevalence of BO in our study population falls just below the lower end of this range. It has been suggested that physicians working in teaching hospitals or academic research centers experience less BO . The fact that 93% of our participants reported affiliation with an academic medical center may contribute to the lower prevalence is noted our study population.…”
Section: Bomentioning
confidence: 99%
“…The 2016 Survey of America's Physicians Practice Patterns and Perspectives found that regulatory/documentation burden, little influence in the direction of the health care system, and loss of clinical autonomy are pivotal . Burnout can lead to patient safety concerns including issues with professionalism, increased risk of medical error and patient/family rapport, and provider safety and wellness …”
Section: Methodsmentioning
confidence: 99%
“…Pediatric EM subspecialty providers are thought to be at high risk for burnout and compassion fatigue . Whereas the practice of pediatrics seems to be protective against burnout, EM continues to top the list of medical specialties at risk .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation